Kanuka honey versus aciclovir for the topical treatment of herpes simplex labialis: a randomised controlled trial. Issue 5 (14th May 2019) - Semprini, Alex; Singer, Joseph; Braithwaite, Irene; Shortt, Nick; Thayabaran, Darmiga; McConnell, Melanie; Weatherall, Mark; Beasley, Richard
Abstract : Objective: To compare New Zealand medical grade kanuka honey with topical aciclovir for the treatment of herpes simplex labialis. Design: Prospective parallel randomised controlled open-label superiority trial. Setting: 76 community pharmacies across New Zealand between 10 September 2015 and 13 December 2017. Participants: 952 adults randomised within the first 72 hours of a herpes simplex labialis episode. Interventions: Random assignment 1:1 to either 5% aciclovir cream or medical grade kanuka honey (90%)/glycerine (10%) cream, both applied five times daily. Outcome measures: The primary outcome was time from randomisation to return to normal skin (stage 7). Secondary outcomes included time from randomisation to stage 4 (open wound), time from stage 4 to 7, maximal pain, time to pain resolution and treatment acceptability. Results: Primary outcome variable: Kaplan-Meier-based estimates (95% CI) for the median time in days for return to normal skin were 8 (8 to 9) days for aciclovir and 9 (8 to 9) for honey; HR (95% CI) 1.06 (0.92 to 1.22), p=0.56. There were no statistically significant differences between treatments for all secondary outcome variables. No related serious adverse events were reported. Conclusion: There was no evidence of a difference in efficacy between topical medical grade kanuka honey and 5% aciclovir in the pharmacy-based treatment of herpes simplex labialis. Trial registration number: ACTRN12615000648527;Post-results